Legal-Civic Reform and Moral Integrity in Indonesian Anti-Corruption Education - Mjolnir Aldeban Mahendra; Ihya Nurina Ratindra (Journal of Civic Education, 2026)
Corruption remains a major challenge to Indonesian democracy, as it erodes public trust, distorts fairness in public services, and weakens the ethical foundations of citizenship. While Indonesia has established legal instruments and anti-corruption institutions, punitive and institutional measures alone are insufficient to address the cultural and moral dimensions of corruption. This article examines the relevance and effectiveness of Zainal Arifin Mochtar’s legal-civic perspective in strengthening legal compliance as well as ethical responsibility among citizens and public officials. Employing a qualitative literature review, the article analyzes academic works, legal scholarship, anti-corruption reports, and civic education studies concerning corruption, institutional reform, integrity education, and citizen participation. The analysis indicates that legal reform and institutional enforcement contribute to strengthening compliance, but their effectiveness depends on broader civic and moral support. Civic participation, integrity education, ethical leadership, and digital transparency play an important role in cultivating deeper anti-corruption awareness. However, these efforts continue to face obstacles, including political interference, inadequate whistleblower protection, uneven implementation of anti-corruption education, and persistent social tolerance toward corrupt practices. This article contributes to civic education scholarship by proposing an integrated legal-civic-moral framework for anti-corruption education in Indonesia.